2021
DOI: 10.1101/2021.04.21.440775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous but not sensory-driven activity controls migration, morphogenesis and survival of adult-born neurons in the mouse olfactory bulb

Abstract: The integration of adult-born neurons in the existent neural circuitry is known to be activity-dependent. To decipher the underlying mechanisms, we genetically manipulated excitability of adult-born cells (via cell-specific overexpression of either Kv1.2 or Kir2.1 K+ channels). Longitudinal in vivo Ca2+ imaging and transcriptome analyses revealed that endogenous but not sensory-driven activity governs migration, morphogenesis, survival, and functional integration of adult-born juxtaglomerular neurons in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 96 publications
(218 reference statements)
1
4
0
Order By: Relevance
“…This result agrees with previous reports of increased migratory and engraftment capacity in developing neurons in the olfactory system after NaChBac expression [228]. Since endogenous Ca 2+ and neuronal activity play essential roles in neuronal migration [289], the endogenous activity of DRG neurons may be associated with this increased migrating capacity.…”
Section: Transplantation Of Nachbac-expressing Drgs Increase Survival...supporting
confidence: 93%
“…This result agrees with previous reports of increased migratory and engraftment capacity in developing neurons in the olfactory system after NaChBac expression [228]. Since endogenous Ca 2+ and neuronal activity play essential roles in neuronal migration [289], the endogenous activity of DRG neurons may be associated with this increased migrating capacity.…”
Section: Transplantation Of Nachbac-expressing Drgs Increase Survival...supporting
confidence: 93%
“…The underlying mechanisms are likely synaptic, including the α7-mediated activation of the Ca 2+ -dependent Ca 2+ /calmodilin-CaMKII-CREB signaling pathway, with the subsequent upregulation of the pCREB-dependent genes (e.g. c-Fos, NMDA receptors, p-TrkB, BDNF) [61], critically important for learning and memory [36, 59]. When starting, as in the current study, the α7 receptor agonist-mediated treatment during the early disease stage, additional advantages are obtained.…”
Section: Discussionmentioning
confidence: 99%
“…4d, P = 0.97, Mann-Whitney test). To test whether longitudinal imaging might enhance the elimination of abJGNs, we compared the fractions of surviving cells in our RGB and Twitch-2B group to a dataset from our laboratory (Li et al, 2021), in which Twitch-2B + abJGNs were imaged only at 2 time points: either at DPI 14 and 25 or DPI 25 and 45. We did not detect any significant difference both at DPI 14/25 (2-time-points group: 62.50 ± 23.41%, n = 5 mice; RGB group: 61.18 ± 24.24%, n = 12 mice; P = 0.65, Mann-Whitney test) and DPI 25/45 (2-time-points group: 80.00 ± 20.76%, n = 5 mice; RGB group: 96.29 ± 7.33%, n = 12 mice; Twitch-2B group: 94.74 ± 4.48%, n = 11 mice; P = 0.07, Kruskal-Wallis test), suggesting that our longitudinal imaging protocol did not promote the elimination of abJGNs.…”
Section: Similar Levels Of Dendritic Complexity and Morphological Plasticity In Eliminated And Surviving Abjgnsmentioning
confidence: 99%
“…It was suggested that fluctuations of [Ca 2+ ]i rather than mere Ca 2+ influx are needed to drive the phosphorylation of nuclear cAMP-response-element-binding protein (CREB; Li et al, , 2009, a known key mediator of the development and survival of ABCs (Giachino et al, 2005;Jagasia et al, 2009;Li et al, , 2021. To determine whether abJGNs were eliminated because their [Ca 2+ ]i was unable to fluctuate, we analyzed the fluctuations of [Ca 2+ ]i both in eliminated and surviving abJGNs (see Methods).…”
Section: Distinct Endogenous Ca 2+ Signaling In Eliminated and Surviving Abjgnsmentioning
confidence: 99%
See 1 more Smart Citation